Comparative analysis of b-learning and e-learning in ICT competencies for teaching in higher education - Flores, Luis; Meléndez, Carlos (Revista Innova Educación, 2021)
Permanent technological training favors teaching and its importance in learning modalities. Therefore, it is proposed to analyze the academic performance of permanent training in ICT skills for teachers and compare the performance of digital learning modalities. The research was quantitative, descriptive, cross-sectional in a higher education institution with continuous training processes. Two editions of courses were considered in which online TIC tools were taught for teachers. The activity records made it possible to analyze the academic performance of permanent training in TIC skills for teachers and compare the learning modalities’ performance through them. In this sense, the results of the teaching-learning process in TIC skills reflect that the evaluations of the first b-learning modality course with 44 participants present a 98% approval rate compared to the second e-learning modality course with 37 participants with an 86% pass rate. The results determine that the management of b-learning promotes a better academic performance of the participants and that the continuous evaluation processes benefit the development of creditable products.